Disease-related responses induced by cadmium in an in vitro human airway tissue model. (15th March 2019) - Xiong, Rui; Wu, Qiangen; Trbojevich, Raul; Muskhelishvili, Levan; Davis, Kelly; Bryant, Matthew; Richter, Patricia; Cao, Xuefei
Highlights: Cadmium is found in tobacco smoke and linked to smoke-related respiratory diseases. Cadmium impaired cilia function in a human air-liquid-interface airway tissue model. Cadmium induced aberrant mucins expression and secretion. Cadmium induced oxidative stress, release of cytokines and matrix metalloproteinases. Cadmium initiated squamous differentiation in this in vitro airway tissue model. Abstract: Cadmium (Cd) is found at high concentrations in tobacco smoke due to its volatility when tobacco is burned. Inhaled Cd is linked to smoking-related respiratory diseases, such as chronic obstructive pulmonary disease and lung cancer. Alterations in mucociliary clearance, squamous metaplasia, and carcinoma are commonly observed in the respiratory tract of animals exposed to Cd. In vitro cell models widely used to study mechanisms underlying Cd toxicity are not suitable for studying its effects on mucociliary clearance and airway tissue remodeling. Herein we assess Cd-induced functional and structural changes in a well-differentiated human air-liquid-interface (ALI) airway tissue model. Acute treatments with Cd induced aberrant expression and secretion of mucins, impaired cilia functions, and squamous differentiation, and produced persistent oxidative stress and enhanced release of pro-inflammatory cytokines and matrix metalloproteinases. Accumulation of intracellular Cd was associated with sustained oxidative stress and inflammation, which, in turn, may have initiated squamous differentiation in ALI cultures. These observations demonstrate that ALI airway tissue models can recapitulate the functional and structural alterations in Cd-exposed animals, suggesting their potential application for studying tissue responses related to respiratory toxicants like those present in tobacco smoke.